The Influence of Utilization of Information Technology and Human Resources Capability on the Performance of Administrative Employees - Syafria Syafria; Supratman Supratman (Universitas Pakuan, 2025)
This research was conducted at SMAN 1 Tilatang Kamang, which is located on Jalan Raya Pekan Kamis, Tilatang Kamang District, Agam Regency. This research is motivated by the initial observations that the author met in the field, there are several problems in the use of information technology used, especially the use of computers, the internet, and printer machines. There are only 10 TU employees, only 2 can operate a computer, and even then, it's just that. If fast electronic data is needed, they find it difficult to make it so they are often assisted by honorary personnel. This study aims to determine the effect of the use of information technology and human resource capabilities on the performance of Administrative Officers (TU) of SMAN 1 Tilatang Kamang. In connection with the research objectives above, a hypothesis is made that